1981
DOI: 10.1021/ic50223a037
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, spectroscopic, and solution studies of imidazolate-bridged dicopper(II) complexes

Abstract: The synthesis and spectroscopic characterization of discrete, water soluble, imidazolate-bridged copper(I1) complexes are reported. Binuclear imidazolate-bridged complexes were crystallized from basic aqueous or methanolic solutions of Cu(pip)2+, pip = 24 (2-(2-pyridyl)ethylimino)methyl]pyridine, or CU(PMDT)~+, PMDT = 1,1,4,7,7-pentamethyldiethylenetriamine, and various substituted imidazoles. The condensation of imidazole-4,5-dicarboxaldehyde with (2-(2-aminoethyl)-pyridine)copper(II) afforded the Cu2bpim3+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 1 publication
2
15
0
1
Order By: Relevance
“…2(b)) due to a partial structural change when the complex is dissolved. This behavior coincides with that of many reported models where the imidazolate bridge is broken in solution or remains only in a narrow range of pH [20,24,25].…”
Section: Uv-vis Spectroscopysupporting
confidence: 91%
“…2(b)) due to a partial structural change when the complex is dissolved. This behavior coincides with that of many reported models where the imidazolate bridge is broken in solution or remains only in a narrow range of pH [20,24,25].…”
Section: Uv-vis Spectroscopysupporting
confidence: 91%
“…Atoms C(2), C(3), C(5), C(6) and C(7) were refined isotropically in two positions (A and B) while all other atoms were refined anisotropically. Although chemical analyses of several subsequent batches of crystals consistently indicated that compound (2) is a tetrahydrate (Kolks, Frihart, Coughlin & Lippard, 1981), only three water molecules were located crystallographically. Two of these, O(W1) and O(WI*), are coordinated to the Cu while the third, O(W2), is lattice water.…”
Section: Determination and Refinement Of The Structures (2)mentioning
confidence: 99%
“…The magnetic exchange coupling constant J for µ-imidazolato bridged dicopper(II) complexes reported so far varies in the range Ϫ10 to Ϫ180 cm Ϫ1 [7Ϫ14, 16,17,21]. Several magneto-structural correlations between the exchange coupling constant J and structural parameters have been proposed [18Ϫ22].…”
Section: Magneto-structural Correlationsmentioning
confidence: 99%